Characterization of volatile bio-chemical compounds in mustard floral honey from apis melifera by gas chromatography-mass spectroscopy - ISHAN ULLAH KHAN,; WIDHI DUBEY,; VEDPRAKASH GUPTA, (International Journal of Pharma and Bio Sciences, 2017)
Honey has been used by humanity for millions of years for nutrition and theraputive purposes. Honey is a very complex natural product, its chemical properties and composition depends not only on the nectar source, but also on other factors such as bee species, geographic area and mode of storage. Honey contains different biological properties, which includes antioxidant characteristic, phenolics. It is a solution of sugars containing secondary metabolites. Flavour and fragrance of honey varies based on the nectar source. The volatile and semi-volatile organic compounds also differ based on nectar collected by honeybees. . Gas Chromatography-Mass Spectroscopy (GC-MS) analysis of unifloral honey samples from mustard collected by Apis melifera was carried out on a Shimadzu GCMS-QP2010 Ultra system. The identification of the chemical compounds was confirmed based on the peak area, retention time and molecular formula from National Institute for Standards and Technology (NIST) mass spectral library, ver. NIST 11. Twenty four4 volatile bioactive compounds were detected. Sugar monosaccharide L-Glyceraldehyde (28.46%) was found in major quantity while other bioactive compounds were detected in trace amounts. Sugar and hydrocarbons constituted 60% of the total composition of mustard honey. Other classes of chemical compounds detected included acids, aldehydes, alcohols, ketones and furans. The terpenes and other phyto-chemical constituents which were present in mustard seed oil were not seen in mustard floral honey. The volatile profile of mustard floral honey was differed from other floral honey which could be used for characterization of mustard honey.